Pola Hubungan Guru Dan Orangtua Dalam Pendidikan Pada Madrasaah Aliyah Negeri Di Aceh Tamiang - Muhammad Saleh (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
Community paradigm of education has changed, one of the things that changes the learning paradigm is the application of cooperation between parents and teachers in learning. Applying the pattern of teacher and parent relations in education at Madrasah Aliyah Negeri in Aceh Tamiang, is a relationship pattern that can establish communication between teachers and parents in education in MAN ManyakPayed and MAN Kualasimpang. This study aims to determine the roles and functions, form of communication, shared responsibility, form of cooperation, form of effort between teachers and parents in MAN ManyakPayed and MAN Kualasimpang in Aceh Tamiang. This research uses qualitative approach. Subjects in this study were teachers and parents at MAN Aceh Tamiang. As for data collection techniques in this study include observation and interviews. Furthermore, Based on the results of data analysis, it is known that the role and function of teachers and parents as partners, guide, direct and supervise. Form of communication is by through an official letter from the school and a visit to the home of his parents in order to know the true condition of the students. The efforts of teachers and parents in MAN and MAN Kualasimpang provide motivation to learn, create a harmonious atmosphere in the family, providing for the needs of children.